Real flue gas CO2 hydrogenation to formate by an enzymatic reactor using O2- and CO-tolerant hydrogenase and formate dehydrogenase - Cha, Jaehyun; Lee, Jinhee; Jeon, Byoung Wook; Kim, Yong Hwan; Kwon, Inchan (Frontiers in Bioengineering and Biotechnology, 2023)
It is challenging to capture carbon dioxide (CO2), a major greenhouse gas in the atmosphere, due to its high chemical stability. One potential practical solution to eliminate CO2 is to convert CO2 into formate using hydrogen (H2) (CO2 hydrogenation), which can be accomplished with inexpensive hydrogen from sustainable sources. While industrial flue gas could provide an adequate source of hydrogen, a suitable catalyst is needed that can tolerate other gas components, such as carbon monoxide (CO) and oxygen (O2), potential inhibitors. Our proposed CO2 hydrogenation system uses the hydrogenase derived from Ralstonia eutropha H16 (ReSH) and formate dehydrogenase derived from Methylobacterium extorquens AM1 (MeFDH1). Both enzymes are tolerant to CO and O2, which are typical inhibitors of metalloenzymes found in flue gas. We have successfully demonstrated that combining ReSH- and MeFDH1-immobilized resins can convert H2 and CO2 in real flue gas to formate via a nicotinamide adenine dinucleotide-dependent cascade reaction. We anticipated that this enzyme system would enable the utilization of diverse H2 and CO2 sources, including waste gases, biomass, and gasified plastics.